Spousal abuse and homicide - Muzvidziwa, Victor N. (International Institute for Human Factor Development, 2016)
Many homes are characterized by violent and conflict ridden environments, a situation many in Southern Africa attribute to culture and tradition. This paper seeks to go beyond explanations of spousal abuse that relate everything to culture and tradition. The notion that spousal abuse is gendered is also rejected. The primary reason for spousal abuse is severe Human Factor (HF) decay. An emerging thread in the paper is the argument that tradition is a double-edged sword, which can also be used to attack practices that justify female domination and subordination. It is also argued that we can invoke tradition to stop exploitative relations or simply to shame those who abuse others in the name of tradition. The paper also tries to show that men and women are active players in the construction of gender relations in the home particularly with regards to spousal abuse and homicide.